Supportive accountability : how to inspire people and improve performance - Melena, Sylvia (La Mesa, CA : Melena Consulting Group, 2018)
Some leaders are too harsh. Some are too lenient. Others are completely disengaged from employee performance management. Striking a delicate balance between supportive leadership and accountability is the key to ensuring employees are as effective and productive as possible. Sylvia Melena is the architect of the Supportive Accountability Leadership(TM) Model, a simple but powerful framework that helps leaders create a motivating work environment while promoting accountability and improving performance.
Includes bibliographical references (pages 245-249).
Keywords: Executive ability; Leadership; Organizational effectiveness; Personnel management; Leadership; Efficiency, Organizational; Personnel Management; Aptitude pour la direction; Leadership; Efficacite organisationnelle; Personnel -- Direction; Executive ability; Leadership; Organizational effectiveness; Personnel management